EDUKASI PENINGKATAN “ACTIVITIES OF DAILY LIVING” PASIEN STROKE MELALUI PENDEKATAN TERAPI KOMPLEMENTER : Strategi Holistik untuk Meningkatkan Kemandirian Pasien Stroke - Hartono, Dodik; Yunita, Rizka; Handayani, Ema (Journal of Health Innovation and Community Services, 2026)
Stroke is one of the main causes of disability that has a significant impact on the decline in patients' Activities of Daily Living (ADL). The limitations of physical and functional abilities after a stroke require comprehensive and sustainable nursing interventions. One approach that can be used is health education combined with complementary therapy as an effort to increase patient independence in carrying out daily activities. The purpose of this community service is to increase knowledge, understanding of patients and families about stroke, improving daily living activities of stroke patients through a complementary therapy approach. This community service is implemented in the form of providing education through a Health education program. This activity was carried out for 2 days at the Holistic Nursing Therapy Probolinggo clinic with a total of 54 participants. The results of the Community Service Program showed an increase in stroke knowledge before being given counseling as many as 65% of participants had poor knowledge and after being given counseling there was an increase in knowledge to 83% of good knowledge. Regarding ADL improvement, 54% of stroke patients had poor knowledge before education, while 87% had improved after education. This community partnership program has had a significant positive impact, as participants have been able to understand and improve their knowledge about stroke, as well as improving Activities of Daily Living (ADL) for stroke patients and their families. This increased level of understanding and knowledge will prevent complications and improve the quality of life for stroke patients.